Facial emotion recognition based music system using convolutional neural networks. (2022) - Sana, S.k.; Sruthi, G.; Suresh, D.; Rajesh, G.; Subba Reddy, G.V.
Abstract: Our face is amongst the most significant body organs. It is critical in determining a person's emotions and feelings. With the use of certain traits discernible on the face, the emotion of an individual can be approximated to a certain degree of precision. With new technology advances, recognizable features of the face can be retrieved as inputs utilizing a webcam. The gathered data helps in determining the mood and songs are played from a customized playlist. This eliminates that time-consuming procedure of physically selecting music or modifying playlists and allowed for the creation of an appropriate playlist dependent on the person's emotional level or mood. We will look at a variety of algorithms to come up with an automatic playlist generating methodology that uses emotion recognition to suggest songs. The facial expression-driven music player is set up in a way that allows you to listen to music based on your facial expression. In this work FER-2013, dataset and CNN algorithm are used for emotion recognition.